Construction and Effect Analysis of a Mixed Actinomycete Flora for Straw Returning to Albic Soil in Northeast China - Xiujie Gong; Yang Yu; Guoyi Lv; Yubo Hao; Lingli Wang; Juntao Ma; Yubo Jiang; Jiahe Zou; Jingyang Li; Qiuju Wang (Microorganisms)
This research targets straw return in Farm 852’s albic soil, China. The soil is nutrient-poor with few microbes and slow straw decomposition. Through fixed-point sampling and bacterial screening, an actinomycete consortium consisting of four strains was assembled, and two of them were identified as new actinomycetes. After 7 days of fermentation, the lignocellulose degradation rates of this consortium outstripped those of single strains, with cellulose degraded at 69.07%, hemicellulose at 64.98%, and lignin at 68.95%. FTIR, XRD, and SEM verified the damage inflicted on the straw structure. Lab simulations found group D (with the consortium) had a higher straw weight loss rate than group C (with commercialized microbial agents) and controls. The compound actinomycetes stepped up the bacterial abundance with the passage of time. In contrast, their effect on fungal abundance was hardly noticeable, but they had markedly ameliorated the soil fertility. These findings prove that the microbial consortium effectively accelerates straw decomposition and boosts soil microbe abundance and fertility in albic soil. It shows great potential for straw return and provides a microbial solution for this field.